Prevalencia del carcinoma epidermoide en el Servicio de Cirugía Cabeza y Cuello del Hospital Nacional Dos de Mayo durante el periodo 2005-2016 - Delesma Chumbe, Angel Frank (2018)
Objective: To evaluate the prevalence of squamous cell carcinoma in the oral cavity in the Head and Neck Surgery Service of a Peruvian hospital during the period 2005-2016. Methods: Descriptive, retrospective, cross-sectional study. We included 4269 biopsies from January 2005 to December 2016, adquired from the records of the Head and Neck Surgery Service of the Dos de Mayo Hospital, Lima, Peru. The diagnosis of squamous cell carcinoma was obtained from the database of the pathological anatomy service of said hospital. The prevalence of squamous cell carcinoma was determined by dividing the total of individuals with said disease over the total biopsied population during that period. Results: From a total of 4,269 biopsies obtained during the period 2005-2016; 80 biopsies were identified with anatomopathological diagnosis of squamous cell carcinoma in the oral cavity. The prevalence of squamous cell carcinoma in the oral cavity was 1.87%. More female than male patients, were affected; in an approximate ratio of 1.4: 1, except between 2009 and 2012, when there was a greater prevalence on male patients. The largest number of cases (28 patients) with squamous cell carcinoma in the oral cavity occurred in patients 41-50 years old, followed by 31-40 years old (16 patients), 61-70 years old (14 patients). Regarding the location of squamous cell carcinoma in the oral cavity, it was manifested mostly in the region of the tongue, followed by the palate, alveolar ridge/ gingiva. Conclusions: The prevalence of squamous cell carcinoma was 1.87%. Females were more affected. It manifested itself more in the 5th decade of life. The location of squamous cell carcinoma in the oral cavity was mostly in the region of the tongue.